I normanni nel territorio dell’Albania del Sud. Il caso di Gurëzeza - Suela Xhyheri; Skënder Muçaj; Skënder Bushi (Bulletin du Centre d’Études Médiévales d’Auxerre)
The purpose of this article is to gather historical and archaeological evidence on the Norman presence in Albania. Indeed, in the spring of 1081 a large Norman army landed on the coast of Vlora and within a short time, conquered the city and strategically important centers : Kanina, Jericho (Orikum), Glavinica, etc., and after they conquered Durrës, Norman armies took the last region the corridor of Vlora up to Prespa, passing through Devoll (Deabolis). After the death of Robert Guiskard (1085) the Normans withdrew from Albania, only to return again in 1107 under the direction of Boemund. After months of exhausting fighting, the Norman army, trapped in the Western Lowland (al. Ultësira Perëndimore), was forced to give up and return to Italy. The presence of the Normans in Glavinica is attested by the headstone inscription found in Ballsh dedicated knight Robert Montefort, which is identified with that of the XI-XII century family lived in Montfort-sur-Risle in Upper Normandy and the second son of Hugo II of Montfort. Of the same period is the castle in Gurëzeza (Mylus) where are located a church and the residential complexes, while in the nearby Mashkjeza is a small military unit, with a keep, a water cistern, a cabin for food stocks and several other rural environments yet undetermined function.